Second-order elections and electoral cycles in democratic Portugal - Freire, A. (South European Society and Politics, 2004)
The aim of this article is to explore the relations between parliamentary,local and European elections in Portugal during the democratic period. In the next section, we briefly introduce the Portuguese political system.Considering the relative importance of the different bodies for its functioning, we would argue that local, regional and European elections are second-order national elections, while parliamentary contests are of the first-order type. We use the definition of first-order and second-order national elections that is now standard in the literature. First-order elections are those where there is much at stake, that is, the control of national executive power. This means that in parliamentary systems, legislative elections are first-order, as are elections for the head of state in presidential regimes. On the contrary, second-order national elections have no direct impact on the control of national executive power.